2022
DOI: 10.3389/fpls.2022.1062055
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem carbon use efficiency in ecologically vulnerable areas in China: Variation and influencing factors

Abstract: Ecologically vulnerable areas (EVAs) are regions with ecosystems that are fragile and vulnerable to degradation under external disturbances, e.g., environmental changes and human activities. A comprehensive understanding of the climate change characteristics of EVAs in China is of great guiding significance for ecological protection and economic development. The ecosystem carbon use efficiency (CUEe) can be defined as the ratio of the net ecosystem productivity (NEP) to gross primary productivity (GPP), one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…In contrast, the grassland ecosystems in those regions benefit from favorable hydrothermal conditions and are often intensively managed or artificially planted, contributing to their higher carbon sink capacity [73][74][75][76]. Additionally, the average CUE value in our study is lower than that reported for other ecosystem types in China, such as forests and farmlands [13,15,77]. Our study primarily concentrates on the grasslands situated in Northern China, where vegetation primarily thrives in cold or arid regions like the Qinghai-Tibet Plateau, northeastern regions, the Loess Plateau, and the Inner Mongolia Plateau.…”
Section: Variations In Cue In Northern Chinese Grasslandscontrasting
confidence: 62%
See 4 more Smart Citations
“…In contrast, the grassland ecosystems in those regions benefit from favorable hydrothermal conditions and are often intensively managed or artificially planted, contributing to their higher carbon sink capacity [73][74][75][76]. Additionally, the average CUE value in our study is lower than that reported for other ecosystem types in China, such as forests and farmlands [13,15,77]. Our study primarily concentrates on the grasslands situated in Northern China, where vegetation primarily thrives in cold or arid regions like the Qinghai-Tibet Plateau, northeastern regions, the Loess Plateau, and the Inner Mongolia Plateau.…”
Section: Variations In Cue In Northern Chinese Grasslandscontrasting
confidence: 62%
“…The carbon flux (NEP and GPP) data were collected from peer-reviewed papers from ISI Web of Science (http://apps.webofknowledge.com (accessed on 19 May 2024)), the China National Knowledge Infrastructure (http://www.cnki.net (accessed on 19 May 2024)), and shared datasets from the National Tibetan Plateau Data Center (https://www.tpdc.ac.cn (accessed on 20 May 2024)), the Science Data Bank (https://www.scidb.cn (accessed on 19 May 2024)), and the Scientific Data Center of CAS (https://www.casdc.cn (accessed on 23 March 2024)), using "Eddy covariance", "Carbon flux", "productivity", "gross primary productivity", "net ecosystem productivity", "net ecosystem exchange (NEE)", "Grassland", and "China" as keywords. To avoid bias in the publication selection, we only selected the literature and datasets that satisfied the following three criteria: (1) the NEP and GPP values were measured using the eddy covariance technique; (2) the data were continuously observed for at least one year; (3) coordinate rotation, WPL correction, night flux calculation, and other adjustments were applied to calibrate the data [13].…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations